ロケット ニヨル デンバ ノ カンソク - 石川, 晴治; イシカワ, ハルジ; 高木, 増美; タカギ, マスミ; 岩田, 晃; イワタ, アキラ; ISHIKAWA, Haruji; TAKAGI, Masumi; IWATA, Akira (国立極地研究所, 1975)
P(論文) 1973年,S-210ロケット4機により,オーロラに伴う電場の観測が行われ,良好なデータを得ることができた.現在解折中でここでは,観測方法に関して報告する. Measurement of the auroral electric field was carried out by the use of small rockets, S-210JA-13, 14, 15 and 18, by the 14th Japanese Antarctic Research Expedition Team. Table 1 is the list of the observations. The record of the observations is now on data processing and the results will be reported in the near future. Hence, here the observation method will be described. departmental bulletin paper